2004
DOI: 10.1080/09540260310001635050
|View full text |Cite
|
Sign up to set email alerts
|

The International Consortium on Mental Health Policy and Services: objectives, design and project implementation

Abstract: The concept of the burden of disease, introduced and estimated for a broad range of diseases in the World Bank report of 1993 illustrated that mental and neurological disorders not only entail a higher burden than cancer, but are responsible, in developed and developing countries, for more than 15% of the total burden of all diseases. As a consequence, over the past decade, mental disorders have ranked increasingly highly on the international agenda for health. However, the fact that mental health and nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Another major concern with GBD was that the impact of subthreshold symptoms was not captured in the DALY. Mental health symptoms that did not meet criteria for diagnosis (as per DSM/ICD nomenclature) are also associated with significant disability [52]. Previous investigation into this issue found that countries with the lowest prevalence estimates for mental disorders also have the highest proportions of cases classified as subthreshold as per DSM-IV criteria and the World Health Organization's Composite International Diagnostic Interview [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Another major concern with GBD was that the impact of subthreshold symptoms was not captured in the DALY. Mental health symptoms that did not meet criteria for diagnosis (as per DSM/ICD nomenclature) are also associated with significant disability [52]. Previous investigation into this issue found that countries with the lowest prevalence estimates for mental disorders also have the highest proportions of cases classified as subthreshold as per DSM-IV criteria and the World Health Organization's Composite International Diagnostic Interview [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Although some isolated initiatives to fund health research based on mental health research priorities have been carried out, most research agencies do not generally allocate their funds according to priorities, quality or relevance of research projects (18, 27). Funding by external donors is also rarely aligned with the needs of LAMI countries (8, 9, 37, 40, 45). Although prioritizing mental health research was one of the 10 recommendations of the 2001 World Health Report (1), continuous efforts are still needed to adequately sensitize donors and policy-makers to the mental health demands of LAMI countries (1, 2, 8, 9, 11, 18, 36, 37, 43, 45, 46).…”
Section: Discussionmentioning
confidence: 99%
“…Funding by external donors is also rarely aligned with the needs of LAMI countries (8, 9, 37, 40, 45). Although prioritizing mental health research was one of the 10 recommendations of the 2001 World Health Report (1), continuous efforts are still needed to adequately sensitize donors and policy-makers to the mental health demands of LAMI countries (1, 2, 8, 9, 11, 18, 36, 37, 43, 45, 46). …”
Section: Discussionmentioning
confidence: 99%
“…are integrated into the structure of the model discussed below. For a detailed discussion of policy issues regarding mental health capacity development in LMIC, see Gulbinat et al (2004) and World Health Organization (2007a; 2007b).…”
Section: Model For Developing Camh Resources In Lmicmentioning
confidence: 99%